Characteristics of Negative and Positive Mental Health Among Nursing Students in the United States. (January 2021) - McDermott, Ryon C.; Fruh, Sharon M.; Williams, Susan; Hauff, Caitlyn; Sittig, Scott; Wright, Theresa; Riley, Bettina; Swanzy, Debra; Graves, Rebecca J.; Hall, Heather
BACKGROUND: Researchers have documented significant psychological problems among nursing students, but findings have been inconclusive as to whether nursing students are "at-risk" for mental health problems compared with their non-nursing peers.AIMS: This study examined whether nursing students have unique mental health characteristics compared with students from other professions.METHOD: Undergraduates ( N = 18, 312; nursing n = 1, 399) were selected from the 2016-2017 National Healthy Minds Study. Participants completed the Patient Health Questionnaire-9 (depression), the Generalized Anxiety Disorder-7 (anxiety), and the Flourishing Scale (positive psychology).RESULTS: Nursing students were equally likely to screen positive for depression and anxiety compared with their non-nursing peers. However, when controlling for gender, age, and year in school, multigroup structural equation modeling analyses revealed that female (but not male) nursing students reported significantly higher levels of specific anxiety symptoms and certain psychological strengths than female students from other professions. Nursing students are equally likely to screen positive for depression or anxiety as their non-nursing peers; however, anxiety disorders may reflect symptom profiles unique to nursing students.CONCLUSIONS: Findings suggest a need for tailored screening and interventions to reduce mental health problems and harness psychological strengths unique to nursing students.